2014
DOI: 10.1039/c4cc05019c
|View full text |Cite
|
Sign up to set email alerts
|

Amine–borane assisted synthesis of wavy palladium nanorods on graphene as efficient catalysts for formic acid oxidation

Abstract: Wavy palladium (Pd) nanorods were obtained by controlled synthesis by using amine-boranes as the reducing agents. Thanks to the unique structure and strong interaction with graphene, the as-synthesized Pd nanorods supported on graphene exhibit much enhanced electrocatalytic activity towards formic acid oxidation as compared with Pd nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
(35 reference statements)
2
8
0
Order By: Relevance
“…Solution‐phase synthesis has been shown to be the most efficient way to control the size and shape of metal nanocrystallites, as it offers diverse parameters for tuning the reaction thermodynamics and kinetics, such as solvents, metal precursors and reductants, capping agents, temperatures, and so on. Oleylamine (OAm) has been widely used in the solution‐phase synthesis of 1D metal nanostructures, because of the many roles it may play in nanocrystal growth, for example, as a mild reducing agent, capping agent, soft template through self‐assembly, and coordinating ligand with metal ions …”
Section: Introductionmentioning
confidence: 99%
“…Solution‐phase synthesis has been shown to be the most efficient way to control the size and shape of metal nanocrystallites, as it offers diverse parameters for tuning the reaction thermodynamics and kinetics, such as solvents, metal precursors and reductants, capping agents, temperatures, and so on. Oleylamine (OAm) has been widely used in the solution‐phase synthesis of 1D metal nanostructures, because of the many roles it may play in nanocrystal growth, for example, as a mild reducing agent, capping agent, soft template through self‐assembly, and coordinating ligand with metal ions …”
Section: Introductionmentioning
confidence: 99%
“…It is also higher than the activity reported in recent literature. For instances, Du et al obtained a peak current of 5.7 A (mg Pd) À1 on Pd nanorods [39]; Mazumder et al showed a 0.2 A (mg Pd) À1 peak current on 7 nm Pd nanoparticles [45].…”
Section: Resultsmentioning
confidence: 98%
“…It has been generally accepted that the formic acid oxidation reaction proceeds on Pd mainly through the ''direct pathway'' without CO poisoning [34,39]. Therefore, it is initialized at potentials which are much more negative than the CO stripping potential.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations